Preparation method of low-carbon salt-resistant modified bentonite

Low-carbon, salt-resistant modified bentonite is prepared through an integrated polymerization-drying process and physical dry mixing technology, which solves the problems of high energy consumption and high cost in the existing technology, maintains the anti-seepage performance of bentonite in a corrosive environment, and is suitable for large-scale production.

CN120757123APending Publication Date: 2025-10-10JIYUAN VOCATIONAL & TECHN COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510793796.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-13
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

Existing methods for preparing modified bentonite have the problems of high energy consumption, high cost and being unfavorable for large-scale production. In particular, in corrosive environments such as high concentrations of cations, strong acids, and strong bases, the anti-seepage barrier properties of bentonite decrease.

Method used

The polymerized bentonite nanocomposite material is prepared by a polymerization-drying integrated process. By physically dry-mixing it with natural bentonite, the process flow is simplified, energy consumption and raw material usage are reduced, and a low-carbon and salt-resistant modified bentonite is prepared.

Benefits of technology

The method realizes the preparation of modified bentonite with low energy consumption and low cost, can maintain good anti-seepage barrier properties in corrosive environments, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120757123A_ABST
    Figure CN120757123A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of low-carbon salt-resistant modified bentonite, which comprises the following steps: preparing bentonite slurry, and uniformly mixing a monomer with the bentonite slurry, an initiator and a cross-linking agent to obtain a mixed solution; carrying out copolymerization on the mixed solution by utilizing a polymerization-drying integrated process to obtain a polymerized bentonite nano composite material; the polymerized bentonite nano composite material is used as a modifier and is physically and dry-mixed with natural bentonite to obtain the low-carbon salt-resistant modified bentonite. Through the polymerization-drying integrated process, the step of independent polymerization is omitted, that is, energy consumption and carbon emission of independent polymerization are omitted; the preparation method disclosed by the invention is simple in process, low in energy consumption and beneficial to large-scale production of the low-carbon modified bentonite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of environmental geotechnical engineering materials, and particularly relates to a method for preparing low-carbon salt-resistant modified bentonite. Background Art

[0002] Bentonite, due to its high swelling and low permeability in aqueous solution, is often used as an anti-seepage barrier material in environmental geotechnical engineering. It is widely used in materials such as soil-bentonite vertical barrier walls, geosynthetic clay liners (GCLs), and compacted clay liners. However, in contaminated sites like landfills, aqueous solutions can become corrosive environments containing high concentrations of cations, strong acids, and strong bases. These conditions inhibit the high swelling and low permeability of bentonite, causing it to lose its barrier properties, posing a significant safety hazard to groundwater.

[0003] Polymer-modified bentonite can effectively solve the above problems. There are two main methods for modifying bentonite. One is to physically dry-mix pure polymer and bentonite according to a mass ratio. Although the process is simple to operate and has low energy consumption, the physical mixing leads to uneven dispersion of the polymer, weak interfacial bonding between the polymer and bentonite, and the polymer easily detaches from the pores of the bentonite, reducing its anti-seepage barrier properties. The other process is to copolymerize the monomer with the bentonite organic initiator in situ. Under the action of the organic initiator, chemical bonds are formed to construct a "bentonite-polymer" intercalation structure. The polymer elution phenomenon of the polymer detaching from the bentonite, as in the former process, is not likely to occur, significantly improving the anti-seepage barrier properties. However, the process is complex and requires multiple steps such as solution mixing, polymerization, drying, crushing, and screening. Due to the large construction site area, the amount of polymerized bentonite required is also large. All bentonite must participate in the polymerization process, which consumes a lot of energy and is not conducive to large-scale production and reducing carbon emissions.

[0004] Therefore, there is an urgent need for a preparation method of low-carbon, salt-tolerant modified bentonite with simple process, low energy consumption and large-scale production. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to address the deficiencies of the above-mentioned prior art and provide a method for preparing a low-carbon, salt-resistant modified bentonite. Compared with the prior art, the preparation method of the present invention mainly solves the problems of excessive energy consumption, high cost and disadvantages of large-scale production from two aspects: process reduction and raw material substitution.

[0006] To solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing low-carbon salt-tolerant modified bentonite, the preparation method comprising the following steps:

[0007] S1, first preparing bentonite slurry, adding monomer, initiator and cross-linking agent to the bentonite slurry and mixing them evenly to obtain a mixed solution;

[0008] S2, copolymerizing the mixed solution obtained in S1 using a polymerization-drying integrated process, and then crushing and sieving to obtain a polymerized bentonite nanocomposite material;

[0009] S3. Physically dry-mixing the polymerized bentonite nanocomposite obtained in S2 with natural bentonite to perform modification to obtain a low-carbon, salt-resistant modified bentonite.

[0010] Preferably, the bentonite slurry in S1 is prepared by uniformly mixing bentonite and deionized water in a mass ratio of 1:15, then allowing the mixture to stand for 48 hours, extracting the upper bentonite suspension to prepare the bentonite slurry; the bentonite is at least one of imported or domestic sodium bentonite, calcium bentonite, and sodium bentonite;

[0011] The monomer is at least one of acrylic acid, sodium acrylate, acrylamide, acrylonitrile, styrene sulfonic acid, starch grafted acrylonitrile, starch grafted acrylic acid, starch grafted acrylamide, cellulose grafted acrylate, vinyl alcohol, vinyl acetate and epichlorohydrin; the initiator is at least one of potassium persulfate, ammonium persulfate, hydrogen peroxide, dibenzoyl peroxide, lauroyl peroxide, peroxydicarbonates and peroxyneodecanoate; the crosslinking agent is N,N'-methylenebisacrylamide, triallyl isocyanurate, divinylbenzene or no crosslinking agent is added.

[0012] Preferably, the mass ratio of the monomer, the bentonite, the initiator and the cross-linking agent in S1 is 1000:(500-1000):6:(0-3).

[0013] Preferably, the steps of the polymerization-drying integrated process in S2 are: polymerizing and drying the mixed solution in a vacuum drying oven at a temperature of 60-80° C. for 16-24 hours; and the sieve particle size used for the sieving is 200 mesh.

[0014] Preferably, the natural bentonite in S3 is sodium bentonite or calcium bentonite; and the mass ratio of the polymerized bentonite nanocomposite material to the natural bentonite is (1-5):5.

[0015] Compared with the prior art, the present invention has the following advantages:

[0016] 1. The present invention utilizes monomers and bentonite to copolymerize and prepare polymerized bentonite nanocomposites through a polymerization-drying integrated process, thereby eliminating the step of separate polymerization, that is, eliminating the energy consumption and carbon emissions of separate polymerization, and reducing process costs.

[0017] 2. The present invention replaces traditional polymers with a self-made polymerized bentonite nanocomposite, using the polymerized bentonite nanocomposite as a modifier for physical dry-mixing with natural bentonite. This reduces the amount of traditional polymer used and is simple to operate. For example, when the polymerized bentonite nanocomposite is produced using a 1:1 mass ratio of monomer to imported sodium bentonite, when dry-mixed with natural bentonite, it can replace 50% of the polymer used compared to conventional processes (i.e., instead of requiring 10% polymer as a modifier, only 5% polymer (polymerized bentonite nanocomposite) + 5% imported sodium bentonite is required). Under the same conditions, this saves 50% of the polymer used and the corresponding carbon emissions compared to using 10% of the traditional polymer for modification.

[0018] 3. This invention utilizes organically initiated polymerization of monomers and bentonite to prepare a polymerized bentonite nanocomposite that can replace traditional polymers. This polymerized bentonite nanocomposite is then physically dry-mixed with natural bentonite in a specific mass ratio to produce low-carbon modified bentonite. This method aims to establish a new low-carbon alternative to dry-mixed modified bentonite that is simple, energy-efficient, and amenable to large-scale production.

[0019] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 (a) is a state diagram of the polymerized bentonite nanocomposite material obtained in Example 2 before and after water absorption, and (b) is a water absorption state diagram of the pure polymer obtained by sodium polyacrylate-acrylamide copolymerization.

[0021] FIG2 (a) is a microstructure diagram of polyacrylamide, and (b) is a microstructure diagram of the polymer nanocomposite material prepared in Example 2. DETAILED DESCRIPTION

[0022] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0023] Example 1

[0024] The preparation method of the low-carbon salt-tolerant modified bentonite in this embodiment comprises the following steps:

[0025] S1. Imported sodium bentonite from Wyoming, USA, and deionized water were mixed uniformly in a mass ratio of 1:15, and then allowed to stand for 48 hours. The upper bentonite suspension was extracted to prepare a sodium bentonite slurry.

[0026] Sodium acrylate, potassium persulfate and N, N'-methylene bisacrylamide are added into the sodium bentonite slurry and mixed uniformly to obtain a mixed solution;

[0027] The mass ratio of the sodium acrylate, the sodium bentonite from Wyoming, USA, the potassium persulfate and the N, N'-methylene bisacrylamide is 1000:1000:6:3;

[0028] S2, the mixed solution obtained in S1 is placed into a vacuum drying box with a temperature of 75℃ for 20 hours for polymerization and drying, and then is crushed and sieved through a 200-mesh screen to obtain the polymerized bentonite nanocomposite;

[0029] S3, the polymerized bentonite nanocomposite obtained in S2 is used as a modifier and physically mixed with the domestic natural sodium bentonite at a mass ratio of 1:5 to obtain the low-carbon salt-resistant modified bentonite.

[0030] In this embodiment, the polymerized bentonite nanocomposite is produced according to a mass ratio of 1:1 of the monomer (sodium acrylate) to the imported sodium bentonite from Wyoming, USA. When mixed with the domestic natural sodium bentonite, 50% of the amount of polymer used in the traditional process can be replaced (i.e., 10% of the polymer is required as a modifier, and now only 5% of the polymer (polymerized bentonite nanocomposite) + 5% of the imported sodium bentonite from Wyoming, USA is required). Under the same conditions, compared with the use of 10% of the traditional polymer for modification, 50% of the amount of polymer and the corresponding carbon emissions can be saved.

[0031] Example 2

[0032] The preparation method of the low-carbon salt-resistant modified bentonite in this embodiment includes the following steps:

[0033] S1, the imported sodium bentonite from Wyoming, USA and deionized water are mixed uniformly at a mass ratio of 1:15, and then are left to stand for 48 hours. The upper bentonite suspension is extracted as a sodium bentonite slurry;

[0034] Sodium acrylate, potassium persulfate and N, N'-methylene bisacrylamide are added into the sodium bentonite slurry and mixed uniformly to obtain a mixed solution;

[0035] The mass ratio of the sodium acrylate, the sodium bentonite from Wyoming, USA, the potassium persulfate and the N, N'-methylene bisacrylamide is 1000:1000:6:3;

[0036] S2, placing the mixed solution obtained in S1 in a vacuum drying oven at a temperature of 75° C. for 22 hours for polymerization and drying, and then pulverizing and passing through a 200-mesh sieve to obtain a polymerized bentonite nanocomposite material;

[0037] S3. The polymerized bentonite nanocomposite material obtained in S2 is used as a modifier and physically dry-mixed with domestic natural sodium bentonite at a mass ratio of 1:5 to obtain a low-carbon salt-resistant modified bentonite.

[0038] Depend on Figure 1 It can be seen that the polymerized bentonite nanocomposite prepared in this example and the pure polymer obtained by copolymerization of sodium polyacrylate-acrylamide have similar properties and both have high water absorption and expansion properties.

[0039] As shown in Figure 2, the polymer nanocomposite prepared in this example forms a three-dimensional network structure composed of linear polymer and bentonite. After absorbing water and swelling, the nanocomposite forms sufficiently large pores, similar to the state of polyacrylamide after water absorption, forming a three-dimensional network structure. This water-absorbing structure fills the pores between the bentonite particles, preventing water from passing through and acting as an anti-seepage barrier.

[0040] Example 3

[0041] The preparation method of the low-carbon salt-tolerant modified bentonite in this embodiment comprises the following steps:

[0042] S1. Mix domestic sodium bentonite and deionized water in a mass ratio of 1:15, then let it stand for 48 hours, and extract the upper bentonite suspension as a sodium bentonite slurry;

[0043] Sodium acrylate, potassium persulfate and N,N'-methylenebisacrylamide are added to the sodium bentonite slurry and mixed evenly to obtain a mixed solution;

[0044] The mass ratio of the sodium acrylate, domestic sodium bentonite, potassium persulfate and N,N'-methylenebisacrylamide is 1000:1000:6:3;

[0045] S2, placing the mixed solution obtained in S1 in a vacuum drying oven at a temperature of 75° C. for 18 hours for polymerization and drying, and then pulverizing and passing through a 200-mesh sieve to obtain a polymerized bentonite nanocomposite material;

[0046] S3. The polymerized bentonite nanocomposite material obtained in S2 is used as a modifier and physically dry-mixed with domestic natural sodium bentonite at a mass ratio of 1:5 to obtain a low-carbon salt-resistant modified bentonite.

[0047] Example 4

[0048] The preparation method of the low-carbon salt-resistant modified bentonite in the embodiment comprises the following steps:

[0049] S1, uniformly mix imported sodium-based bentonite from Wyoming, USA and deionized water at a mass ratio of 1:15, then stand for 48 hours, extract the upper bentonite suspension as a sodium-based bentonite slurry;

[0050] Add sodium acrylate, acrylamide and potassium persulfate into the sodium-based bentonite slurry and mix uniformly to obtain a mixed solution;

[0051] The mass ratio of the mixed monomers of sodium acrylate and acrylamide, the sodium-based bentonite from Wyoming, USA and potassium persulfate is 1000:500:6; the mass ratio of sodium acrylate to acrylamide in the mixed monomers is 1:2;

[0052] S2, place the mixed solution obtained in S1 into a vacuum drying box at a temperature of 80℃ for 16 hours for polymerization and drying, then crush and pass through a 200-mesh sieve to obtain a polymerized bentonite nanocomposite;

[0053] S3, use the polymerized bentonite nanocomposite obtained in S2 as a modifier, physically dry-mix it with domestic natural calcium-based bentonite at a mass ratio of 2:5 to obtain a low-carbon salt-resistant modified bentonite.

[0054] Example 5

[0055] The preparation method of the low-carbon salt-resistant modified bentonite in the embodiment comprises the following steps:

[0056] S1, uniformly mix domestic sodium-based bentonite and deionized water at a mass ratio of 1:15, then stand for 48 hours, extract the upper bentonite suspension as a sodium-based bentonite slurry;

[0057] Add sodium acrylate, potassium persulfate and N,N'-methylenebisacrylamide into the sodium-based bentonite slurry and mix uniformly to obtain a mixed solution;

[0058] The mass ratio of sodium acrylate, the sodium-based bentonite from Wyoming, USA, potassium persulfate and N,N'-methylenebisacrylamide is 1000:500:6:3;

[0059] S2, place the mixed solution obtained in S1 into a vacuum drying box at a temperature of 60℃ for 24 hours for polymerization and drying, then crush and pass through a 200-mesh sieve to obtain a polymerized bentonite nanocomposite;

[0060] S3, use the polymerized bentonite nanocomposite obtained in S2 as a modifier, physically dry-mix it with domestic natural calcium-based bentonite at a mass ratio of 2:5 to obtain a low-carbon salt-resistant modified bentonite.

[0061] Example 6

[0062] The preparation method of the low-carbon salt-tolerant modified bentonite in this embodiment comprises the following steps:

[0063] S1. Imported sodium bentonite from Wyoming, USA, and deionized water were mixed uniformly in a mass ratio of 1:15, and then allowed to stand for 48 hours. The upper bentonite suspension was extracted to prepare a sodium bentonite slurry.

[0064] Adding acrylonitrile, ammonium persulfate and triallyl isocyanurate into sodium bentonite slurry and mixing evenly to obtain a mixed solution;

[0065] The mass ratio of acrylonitrile, sodium bentonite from Wyoming, USA, ammonium persulfate and triallyl isocyanurate is 1000:1000:6:3;

[0066] S2, placing the mixed solution obtained in S1 in a vacuum drying oven at a temperature of 75° C. for 19 hours for polymerization and drying, and then pulverizing and passing through a 200-mesh sieve to obtain a polymerized bentonite nanocomposite material;

[0067] S3. The polymerized bentonite nanocomposite material obtained in S2 is used as a modifier and physically dry-mixed with domestic natural sodium bentonite at a mass ratio of 3:5 to obtain a low-carbon salt-resistant modified bentonite.

[0068] Example 7

[0069] The preparation method of the low-carbon salt-tolerant modified bentonite in this embodiment comprises the following steps:

[0070] S1. Imported sodium bentonite from Wyoming, USA, and deionized water were mixed uniformly in a mass ratio of 1:15, and then allowed to stand for 48 hours. The upper bentonite suspension was extracted to prepare a sodium bentonite slurry.

[0071] Adding acrylonitrile, starch-grafted acrylic acid, potassium persulfate and divinylbenzene to sodium bentonite slurry and mixing evenly to obtain a mixed solution;

[0072] The mass ratio of the mixed monomer of acrylonitrile and starch grafted acrylic acid, sodium bentonite from Wyoming, USA, potassium persulfate and divinylbenzene is 1000:1000:6:3; the mass ratio of acrylonitrile and starch grafted acrylic acid in the mixed monomer is 1:1;

[0073] S2, placing the mixed solution obtained in S1 in a vacuum drying oven at a temperature of 75° C. for 24 hours for polymerization and drying, and then pulverizing and passing through a 200-mesh sieve to obtain a polymerized bentonite nanocomposite material;

[0074] S3. The polymerized bentonite nanocomposite material obtained in S2 is used as a modifier and physically dry-mixed with domestic natural sodium bentonite at a mass ratio of 1:1 to obtain a low-carbon salt-resistant modified bentonite.

[0075] The initiator in S1 of this embodiment can also be ammonium persulfate, hydrogen peroxide, dibenzoyl peroxide, lauroyl peroxide, peroxydicarbonate or peroxyneodecanoate; the cross-linking agent can also be triallyl isocyanurate or divinylbenzene; the monomer can also be at least one of acrylamide, acrylonitrile, styrene sulfonic acid, starch grafted acrylonitrile, starch grafted acrylic acid, starch grafted acrylamide, cellulose grafted acrylate, vinyl alcohol, vinyl acetate and epichlorohydrin; the mass ratio of the polymerized bentonite nanocomposite material and the natural bentonite in S3 can also be 4:5.

[0076] Taking natural sodium bentonite as a comparative example, the permeability coefficients of the low-carbon salt-tolerant modified bentonite materials prepared in the above Examples 1-7 and the comparative example natural sodium bentonite were tested, and the results are shown in Table 1.

[0077] Table 1 Permeability coefficient of low carbon modified bentonite obtained in Examples 1-7

[0078] 0.3 mol / L NaCI <![CDATA[0.03mol / LCaCl2]]> Comparative Example <![CDATA[7.51×10 -9 m / s]]> <![CDATA[6.08×10 -9 m / s]]> Example 1 <![CDATA[5.23×10 -11 m / s]]> <![CDATA[1.09×10 -11 m / s]]> Example 2 <![CDATA[8.95×10 -11 m / s]]> 2.69 x 10 -11 m / s Example 3 1.25 x 10 -11 m / s <![CDATA[8.39×10 -10 m / s]]> Example 4 7.39 x 10 -11 m / s 1.92 x 10 -11 m / s Example 5 <![CDATA[6.43×10 -11 m / s]]> <![CDATA[1.37×10 -11 m / s]]> Example 6 <![CDATA[4.39×10 -11 m / s]]> <![CDATA[5.43×10 -11 m / s]]> Example 7 <![CDATA[2.75×10 -11 m / s]]> <![CDATA[3.12×10 -11 m / s]]>

[0079] As can be seen from Table 1, the permeability coefficients of the low-carbon, salt-tolerant modified bentonite materials prepared in Examples 1-7 are basically the same as those of the existing natural sodium-based bentonite, but the preparation method of the present invention has the advantages of low cost, low carbon, and large-scale production.

[0080] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent variation made to the above embodiment based on the essence of the invention technology shall still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing low-carbon salt-tolerant modified bentonite, characterized in that: The preparation method comprises the following steps: S1, first preparing bentonite slurry, adding monomer, initiator and cross-linking agent to the bentonite slurry and mixing them evenly to obtain a mixed solution; S2, copolymerizing the mixed solution obtained in S1 using a polymerization-drying integrated process, and then crushing and sieving to obtain a polymerized bentonite nanocomposite material; S3. Physically dry-mixing the polymerized bentonite nanocomposite obtained in S2 with natural bentonite to perform modification to obtain a low-carbon, salt-resistant modified bentonite.

2. The method for preparing a low-carbon salt-tolerant modified bentonite according to claim 1, wherein: The bentonite slurry described in S1 is prepared by uniformly mixing bentonite and deionized water at a mass ratio of 1:15, then allowing the mixture to stand for 48 hours, extracting the upper bentonite suspension to prepare the bentonite slurry; the bentonite is at least one of imported or domestic sodium bentonite, calcium bentonite, and sodium bentonite; The monomer is at least one of acrylic acid, sodium acrylate, acrylamide, acrylonitrile, styrene sulfonic acid, starch grafted acrylonitrile, starch grafted acrylic acid, starch grafted acrylamide, cellulose grafted acrylate, vinyl alcohol, vinyl acetate and epichlorohydrin; the initiator is at least one of potassium persulfate, ammonium persulfate, hydrogen peroxide, dibenzoyl peroxide, lauroyl peroxide, peroxydicarbonates and peroxyneodecanoate; the crosslinking agent is N,N'-methylenebisacrylamide, triallyl isocyanurate, divinylbenzene or no crosslinking agent is added.

3. The method for preparing a low-carbon salt-tolerant modified bentonite according to claim 2, wherein: The mass ratio of the monomer, the bentonite, the initiator and the cross-linking agent in S1 is 1000:(500-1000):6:(0-3).

4. The method for preparing a low-carbon salt-tolerant modified bentonite according to claim 1, wherein: The steps of the polymerization-drying integrated process in S2 are: polymerizing and drying the mixed solution in a vacuum drying oven at a temperature of 60-80° C. for 16-24 hours; the sieve particle size used for the sieving is 200 mesh.

5. The method for preparing a low-carbon salt-tolerant modified bentonite according to claim 1, wherein: The natural bentonite in S3 is sodium bentonite or calcium bentonite; the mass ratio of the polymerized bentonite nanocomposite material to the natural bentonite is (1-5):5.